“After the Dust Settles”: Foucauldian Narratives of Retired Athletes' “Re-orientation” to Exercise - Jones, Luke; Avner, Zoe; Denison, Jim (Frontiers in Sports and Active Living, 2022)
One aspect of sports retirement that has been overlooked until recently is the manner in which retired athletes relate to, and seek to redefine, the meaning of exercise in their post-sport lives. In this article, three Foucauldian scholars present and analyze a series of vignettes concerning their own sense-making and meaning-making about exercise following their long-term involvement in high-performance soccer (authors one and two) and distance running (author three). In doing so, this paper not only underlines both the problematic legacy of high-performance sport for retiring athletes’ relationship to movement and exercise, but also how social theory, and Foucauldian theorization in particular, can serve to open new spaces and possibilities for thinking about sports retirement.